2019
DOI: 10.2139/ssrn.3380592
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Industrial and Entrepreneurial Jobs on Youth: 5-Year Experimental Evidence on Factory Job Offers and Cash Grants in Ethiopia

Abstract: We study two interventions for underemployed youth across five Ethiopian sites: a $300 grant to spur self-employment, and a job offer to an industrial firm. Despite significant impacts on occupational choice, income, and health in the first year, after five years we see nearly complete convergence across all groups and outcomes. Shortrun increases in productivity and earnings from the grant dissipate as recipients exit their micro-enterprises. Adverse effects of factory work on health found after one year also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…Our findings suggest it is sensible to revisit subjects in RCTs as the measured impacts of interventions may evolve markedly over time. The results echo those of Blattman et al (2019) who also find that short-term effects of employment interventions (in their case, in the form of cash grants and random job offerings in the manufacturing sector in Ethiopia) taper off over time and eventually dissipate completely. There exists a potential downsize to these disappointing results that extend beyond the variables that we measure.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our findings suggest it is sensible to revisit subjects in RCTs as the measured impacts of interventions may evolve markedly over time. The results echo those of Blattman et al (2019) who also find that short-term effects of employment interventions (in their case, in the form of cash grants and random job offerings in the manufacturing sector in Ethiopia) taper off over time and eventually dissipate completely. There exists a potential downsize to these disappointing results that extend beyond the variables that we measure.…”
Section: Discussionsupporting
confidence: 72%
“…andFilmer et al (2014) review the evidence and conclude there is considerable support for the hypothesis that such interventions 'work'. However,Blattman et al (2019) are critical about the long-term impacts of a cash grant intervention in Ethiopia-positive impacts of the capital injection (and job offer intervention) had dissipated after 5 years.4 Steinert et al (2018) examine the impact of a financial literacy training combined with a psychosocial parenting intervention for 552 households in South Africa and show that the combined program has substantial positive effects on financial behaviour. However, this study also does not consider labour market effects.5 Adoho et al (2014) evaluate bundled interventions for adolescent girls in Liberia incorporating vocational training and other components including business skills training and empowerment activities.…”
mentioning
confidence: 99%
“…McKenzie and Woodruff (2017) points out, most of the existing literature on business training does not examine the effects of the training at different points in time. The few exceptions indicate that some effects disappear in the longer term (e.g., Blattman, Fiala and Martinez, 2020;Blattman, Dercon and Franklin, 2019). Furthermore, while SEED explicitly features soft skills (with two distinct intensities) as a centerpiece of its curriculum, we only observe differences in inter-personal skills and self-efficacy between the two treatment arms, but no statistical differences overall for economic outcomes.…”
Section: Discussionmentioning
confidence: 61%
“…After four years, their business assets climbed by 57%, work hours by 17%, and earnings by 38% (Blattman et al, 2013). However, a recent study found that the effects appear to diminish as grant recipients close their enterprises indicating that the obstacles to income or self-employment can be difficult to be resolved through one-off and unidimensional interferences (Blattman et al, 2022). In Asia, the likelihood of participants in urban regions engaging in entrepreneurial endeavours is greater than in rural locations (Hanri, 2018), which the high cost of living may cause.…”
Section: Cash Transfer and Entrepreneurshipmentioning
confidence: 99%